2019
DOI: 10.1155/2019/4150279
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Mitigative Effect of Controlled Permeable Formwork (CPF) Liner on Early-Age Shrinkage of Box-Girder Concrete

Abstract: Because of its high binder content and severe construction environment, early-age cracking is one of the most important threats to concrete used in continuous box-girder bridge structures. In this study, controlled permeable formwork (CPF) liner was used to mitigate the early-age shrinkage and reduce the early-age cracking risk of box-girder concrete. Early-age shrinkage was measured by a noncontact method and started at 30 min after adding mix water until 7 d. Internal relative moisture content and pore distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The application of CPFL can drain out air bubbles and water while retaining fine particles like cement, which would lead to a reduced water to binder ratio and the improved structure of the concrete surface [ 22 , 37 , 38 ]. Furthermore, water absorbed by the CPFL would be also released to compensate the RH drop of concrete cover [ 23 ]. All of these characteristics are beneficial for reducing the drying shrinkage of concrete.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of CPFL can drain out air bubbles and water while retaining fine particles like cement, which would lead to a reduced water to binder ratio and the improved structure of the concrete surface [ 22 , 37 , 38 ]. Furthermore, water absorbed by the CPFL would be also released to compensate the RH drop of concrete cover [ 23 ]. All of these characteristics are beneficial for reducing the drying shrinkage of concrete.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, controlled permeable formwork liner (CPFL) is also an effective technology that improves the quality of cover concrete [ 21 , 22 ]. It has been confirmed that CPFL covered on the surface of concrete mitigated early age shrinkage effectively, due to the improved internal relative moisture content of surface concrete [ 23 ]. In this study, we focused on the impacts of several shrinkage-reducing measures, including adding SAP, SRA and applying CPF liner, on the shrinkage performance of concrete containing iron tailing sand.…”
Section: Introductionmentioning
confidence: 99%